Altered Knee Loading Following Primary ACL Repair versus ACL Reconstruction - Steven Singleton; Harrison Scofield; Brittany Davis; Alexandra Waller; Craig Garrison; Shiho Goto; Joseph Hannon (North American Sports Medicine Institute, 2023)
# Background ACL repair (ACL-r) has recently gained renewed clinical interest for treatment of ACL tears. ACL-r has several potential benefits over ACL reconstruction (ACL-R) including maintaining the native ACL innervation and blood supply, no graft site morbidity, and possible improved knee biomechanics and decrease in osteoarthritis. The purpose of this study was to assess for differences in metrics of knee joint loading during a single limb squat task between individuals following a primary ACL-r versus those who underwent a standard ACL-R with a patella bone-tendon-bone autograft. # Study type Case Control Study # Methods The ACL-r group \[n: 15, age(yrs): 38.8±13.9\] sustained a proximal ACL disruption that was amenable to repair, while the ACL-R group \[n: 15, age(yrs): 25.60±1.7\] underwent primary reconstruction with patella bone-tendon-bone autograft. At 12-weeks post-operation, both groups completed the IKDC questionnaire and biomechanical testing during performance of the single limb squat. Bilateral peak knee extension moment and total knee joint power as a measure of eccentric loading (contraction) during the descent phase of the squat were calculated on the surgical and non-surgical limb and averaged across the middle three of five trials. Participants also completed quadriceps strength testing on both limbs three months after surgery on an isokinetic dynamometer at 60°/sec. LSI (Limb Strength Index) was calculated for all variables. Separate ANCOVAs were performed on each biomechanical variable to examine differences between groups. # Results The ACL-r had a significantly greater peak knee extension moment LSI (ACL-r: 78.46±5.79%; ACL-R: 56.86±5.79%; p=0.019, ηp2=.186) and total knee joint power LSI (ACL-r: 72.47±7.39%; ACL-R: 39.70±7.39%, p=0.006, ηp2=.245) than the ACL-R group. The ACL-r also had a significantly greater quadriceps LSI than the ACL-R group (ACL-r: 66.318±4.61%, ACL-R: 48.03±4.61%, p=0.013, ηp2=.206). # Conclusions Individuals following ACL-r demonstrate increased knee joint loading symmetry during a single leg squat task and greater quadriceps strength symmetry at 12 weeks post-surgery compared to those who underwent ACL-R. # Level of Evidence 3